Using fractional exhaled nitric oxide to guide step-down treatment decisions in patients with asthma: a systematic review and individual patient data meta-analysis. Issue 5 (21st May 2020) - Wang, Kay; Verbakel, Jan Y.; Oke, Jason; Fleming-Nouri, Alexander; Brewin, Josh; Roberts, Nia; Harada, Norihiro; Atsuta, Ryo; Takahashi, Kazuhisa; Mori, Kazutaka; Fujisawa, Tomoyuki; Shirai, Toshihiro; et al.
Background: High exhaled nitric oxide fraction ( F ENO ) levels are associated with greater risk of asthma exacerbation. However, it is not clear how F ENO can be used to guide safe reductions in inhaled corticosteroid (ICS) doses in asthma patients. This study assesses the ability of F ENO to guide ICS reductions. Methods: Systematic searching of electronic databases identified prospective observational studies and randomised controlled trials which recruited participants with mild-to-moderate asthma aged ≥12 years and measured F ENO before reducing ICS. We performed multilevel mixed-effects logistic regression in relation to acute exacerbations and estimated each participant's exacerbation risk using our logistic regression model. Results: We included data from seven out of eight eligible studies, representing 384 participants. ICS doses were halved in four studies and withdrawn in three studies. A baseline F ENO measurement of ≥50 ppb was associated with increased risk of exacerbations (crude OR 3.14, 95% CI 1.41–7.00, p=0.005; adjusted OR 3.08, 95% CI 1.36–6.98, p=0.007) and corresponded to an estimated exacerbation risk cut-off of 15%. Reducing ICS when estimated exacerbation risk was <15% versus <10% would result in fewer patients remaining on the same ICS dose (40 (10.4%) out of 384 versus 141 (36.7%) out of 384), but similar proportions of patients avoiding exacerbations (222 (91.4%) out of 243, 95% CI 87.1–94.6% versus 311 (90.4%) out of 344, 95% CI 86.8–93.3%). Conclusion: In patients with mild-to-moderate asthma, gradual ICS reduction when F ENO is <50 ppb may help decrease ICS use without increasing exacerbations. Future research should aim to validate these findings in larger populations. In nonsmoking patients with mild-to-moderate well-controlled asthma, stepping down treatment when F ENO is <50 ppb reduces prescribing of inhaled corticosteroids without increasing exacerbations http://bit.ly/2SKaxSt